2012
DOI: 10.1186/1476-069x-11-5
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer and toxicity from critical use exemptions of methyl bromide: Environmental protection helps protect against human health risks

Abstract: BackgroundAlthough ozone-depleting methyl bromide was destined for phase-out by 2005, it is still widely applied as a consequence of various critical-use-exemptions and mandatory international regulations aiming to restrict the spread of pests and alien species (e.g. in globalized transport and storage). The withdrawal of methyl bromide because of its environmental risk could fortuitously help in the containment of its human toxicity.MethodsWe performed a systematic review of the literature, including in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(48 citation statements)
references
References 73 publications
(129 reference statements)
0
45
0
Order By: Relevance
“…Fumigation is a widely used method to prevent a multitude of pests, i.e. fungi and arthropods, from destroying natural products and spread worldwide during transport [2]. Previous studies in the harbours of Hamburg and Rotterdam have identified high frequencies of containers contaminated with fumigants and other industrial chemicals, such as methyl bromide and formaldehyde, the concentration of which in many cases exceeded the chronic recommended exposure levels [1,3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fumigation is a widely used method to prevent a multitude of pests, i.e. fungi and arthropods, from destroying natural products and spread worldwide during transport [2]. Previous studies in the harbours of Hamburg and Rotterdam have identified high frequencies of containers contaminated with fumigants and other industrial chemicals, such as methyl bromide and formaldehyde, the concentration of which in many cases exceeded the chronic recommended exposure levels [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…The main targets of toxic effect are the respiratory and the nervous system. Ethylene oxide, formaldehyde and benzene can damage DNA and induce cancer as recognised by the International Agency for Research on Cancer, while some fumigants, such as methyl bromide, are suspected carcinogens [2,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…As there is a lack of alternative and similarly cost-effective fumigants, numerous exemptions, especially in agriculture (Norman 2005) and in the transport industry (Budnik et al 2012), have been applied for.…”
Section: Re-evaluationmentioning
confidence: 99%
“…Peak exposures and intoxication due to improper handling of the fumigant, often together with a lack of or inadequate protective clothing occur frequently. Increasingly there are also unexpected exposures in the transport sector, for example when handling or transshipping transport containers (Breeman 2009;Budnik et al 2012). …”
Section: External Exposurementioning
confidence: 99%
“…To control the Fusarium wilt, growers use systemic fungicides like methyl bromide [1], chloropicrin and benomyl [2]. Beside the fact that these chemicals are toxic to humans and the environment [3], they can also cause selection for resistant mutated pathogen [4].…”
Section: Introductionmentioning
confidence: 99%